2001
DOI: 10.1002/ijc.10170
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the antibody repertoire of astrocytoma patients against antigens expressed by gliomas

Abstract: The molecular characterization of antigens preferentially or exclusively expressed by astrocytomas and recognized by the autologous immune system are a prerequisite for the development of specific vaccines. To identify such antigens, we screened 5 cDNA expression libraries derived from astrocytomas and other gliomas for reactivity with high-titered IgG antibodies in the sera of astrocytoma patients using SEREX, the serologic identification of antigens by recombinant cDNA expression cloning. Autologous and allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 18 publications
1
42
0
1
Order By: Relevance
“…This finding was supported by a large-scale DNA microarray analysis on primary breast tumors from 117 young patients, showing that BI-1 (TEGT) expression is up-regulated in breast cancer and co-regulates with the expression of the estrogen receptor-␣ gene. 14 Furthermore, Schmitts and co-workers 15 reported that BI-1 expression was between 5 and 10 times stronger in 16 glioma samples tested compared with normal brain and other normal tissues. Finally, microarray analyses of the expression levels of more than 8900 different human genes in a set of normal and malignant prostate tissues revealed that BI-1 (TEGT) is highly and specifically expressed in malignant samples.…”
Section: Array and Northern Blot Analysis Of Bi-1 Expression In Prostmentioning
confidence: 99%
“…This finding was supported by a large-scale DNA microarray analysis on primary breast tumors from 117 young patients, showing that BI-1 (TEGT) expression is up-regulated in breast cancer and co-regulates with the expression of the estrogen receptor-␣ gene. 14 Furthermore, Schmitts and co-workers 15 reported that BI-1 expression was between 5 and 10 times stronger in 16 glioma samples tested compared with normal brain and other normal tissues. Finally, microarray analyses of the expression levels of more than 8900 different human genes in a set of normal and malignant prostate tissues revealed that BI-1 (TEGT) is highly and specifically expressed in malignant samples.…”
Section: Array and Northern Blot Analysis Of Bi-1 Expression In Prostmentioning
confidence: 99%
“…13 Furthermore, BI-1 is highly expressed in tumor cells such as human prostate cancer, human breast cancer, human brain tumor, or large cell lymphoma. 12,[14][15][16]30 In addition, in this work, we found BI-1 to be expressed in primary AML-blasts and -cell lines. Consistent with these findings, small-interfering RNAmediated inhibition of BI-1 expression in different prostate carcinoma cell lines led to caspase-3 activation and spontaneous apotosis.…”
Section: Discussionmentioning
confidence: 69%
“…11 BI-1 gene expression is accentuated not only in tissues with low apoptotic activity, such as the epithelium of the developing lung, but also in several human malignant tumors, such as prostate carcinoma, breast carcinoma, and brain tumors. [12][13][14][15] Grzmil et al 16 were able to increase spontaneous apoptosis rates in prostate carcinoma cell lines by suppressing BI-1 expression using specific small-interfering RNA. Lee et al 17 presented evidence that BI-1 regulates generation of reactive oxygen species in the context of endoplasmic reticulum stress and thus inhibits apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of BI-1 expression differ in different human cancers-while breast, glioma, prostate, uterine and ovarian cancers show two and above fold upregulation (Schmits et al, 2002;del Carmen Garcia Molina Wolgien et al, 2005;Grzmil et al, 2006), stomach, colon, kidney, lung and rectal cancers exhibit twofold downregulation of BI-1 (Grzmil et al, 2006). It is unknown whether these changes are relevant to the cancerous state or are simply a reflection of different levels of BI-1 in these tissues during development (for example, BI-1 expression is inhibited during lung development and was found to be downregulated in lung cancer).…”
Section: Bi-1 and Cancermentioning
confidence: 99%